(untitled) (International Journal of Innovative Research in Computer Science & Technology, 2020)
In today`s world, many users like to use media player in order to solve the complex functions and large memory requirement in a smart phone. With a rapid growth of network and technology, multimedia technology is used in media players. As the Android based devices are getting more popular among the people, an Android based application attracts more attention. Based on Android technology and java language the design and coding of a simple, convenient, less memory requirement as well as user friendly multimedia player is shown in this paper. The player is designed in such a way to obtain higher performance; simple operations and run on the Android based mobile devices. The papers discuss about the study of multimedia player with the help of already existing media players which are available openly in the Android market and proposed system for multimedia player that will be providing the uninterrupted enjoyment for the users.